The Effect of External Electric Field on AlH Radical (Journal of Atomic and Molecular Sciences, 2021)
Using the density functional B3P86/cc-PV5Z method, the geometric structureof AlH molecule under different external electric fields are optimized, and thebond lengths, dipole moments, vibration frequencies and other physical propertiesparameters are obtained. The potential energy curves under different external fieldsare also obtained by CCSD(T) method with the same basis set. These results showthat the properties parameters and potential energy curves may change with differentexternal electric field, especially in the reverse electric fields. The potential energyfunction without external electric field is fitted by Morse potential, and the potentialenergy curves under different external fields are fitted using constructed potentialmodel, which adopted the dipole approximation theory. It is found that the fittingparameters are good agreement with experimental values and the critical dissociationelectric parameter is consistent with numerical calculation. These results will provideimportant theoretical and experimental reference for further studying the molecularspectrum, dynamics and molecular cooling with Stark effect.
Keywords: AlH radical; potential function; external electric field.